2013
DOI: 10.1037/a0031357
|View full text |Cite
|
Sign up to set email alerts
|

Frontal and posterior subtypes of neuropsychological deficit in Parkinson's disease.

Abstract: Mild cognitive impairment in Parkinson's disease (PD) is heterogeneous in regard to affected domains. Although patterns of cognitive performance that may predict later dementia are as yet undetermined, posterior-versus frontal-type assessments show promise for differential predictive value. The present study included 70 individuals: 42 with idiopathic PD without dementia and 28 age- and education-matched healthy control adults (HC). Participants completed assessments of cognition with emphasis on tests that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 43 publications
1
26
0
1
Order By: Relevance
“…In a sample of 42 non-demented PD participants and 28 control participants, 36% of the PD group showed deficits (defined at 1.5 SD below the control-group mean) on TMT-B, while only 15% showed deficits on Digit Span Forward and Digit Span Backward, suggesting that TMT-B performance may be affected to a greater extent than Digit Span in early PD (Miller et al, 2013). Anxiety may impair cognitive performance, especially on complex or attentionally demanding tasks (Derakshan & Eysenck, 2009), which may explain the observed association between anxiety and TMT-B, and the lack of association between anxiety and a relatively simple task (Digit Span Forward) in our sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a sample of 42 non-demented PD participants and 28 control participants, 36% of the PD group showed deficits (defined at 1.5 SD below the control-group mean) on TMT-B, while only 15% showed deficits on Digit Span Forward and Digit Span Backward, suggesting that TMT-B performance may be affected to a greater extent than Digit Span in early PD (Miller et al, 2013). Anxiety may impair cognitive performance, especially on complex or attentionally demanding tasks (Derakshan & Eysenck, 2009), which may explain the observed association between anxiety and TMT-B, and the lack of association between anxiety and a relatively simple task (Digit Span Forward) in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Visuospatial, attentional, and executive deficits are the most typical in PD individuals with mild cognitive impairment (PD-MCI) (Aarsland, Bronnick, & Fladby, 2011). In a recent study of individuals with mild to moderate PD with neither dementia nor mild cognitive impairment, measures of attention and executive function (frontal-type tests) were the most sensitive to cognitive compromise (Miller, Neargarder, Risi, & Cronin-Golomb, 2013). Understanding cognitive deficits in the early stages of the disease is important because they may predict the progression of cognitive dysfunction to dementia (Azuma, Cruz, Bayles, Tomoeda, & Montgomery, 2003; Kehagia, Barker, & Robbins, 2010; Levy et al, 2002; Williams-Gray et al, 2009; Williams-Gray et al, 2007).…”
mentioning
confidence: 99%
“…The second cluster of PD patients show decline in non-frontal cognitive functions (such as visuospatial abilities, Miller et al, 2013), and the presence of these cognitive dysfunctions during early stages of the disease predicts rapid progression to PDD (Robbins and Cools, 2014;Williams-Gray et al, 2009). PDD is a form of dementia which has been attributed to the degeneration of temporal and parietal cortical areas and the nucleus basalis of Meynert (Gratwicke et al, 2015;Kehagia et al, 2013).…”
Section: General Conclusion Open Questions and Directions For Futumentioning
confidence: 99%
“…This issue was investigated by Miller et al [23] who studied the neuropsychological, clinical and demographic features of frontal and posterior cognitive subtypes compared with those with neither deficit. They found that the subtype with neither deficit had less severe motor impairment, but there were otherwise no clinical or demographic differences.…”
Section: Cross-sectional Associations Of Subtypes With Other Clinicalmentioning
confidence: 99%